Training and Work Motivation on The Performance of PT. Wings Surya Bangkalan Employees - Nugraha, Dimas Ardi; Ananta Fanni Aprlia; Robaitul Awaliyah; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research uses a qualitative approach with a case study type to understand training program planning and work motivation at PT Wings Surya Bangkalan. The research subjects consisted of company managers and one of the employees. Data collection techniques include interviews, observation and documentation. The research results show that the training and work motivation program at PT Wings Surya Bangkalan aims to increase the understanding and motivation of employees with various backgrounds. Training is carried out regularly, and there is also refresher training for employees who have worked for a long time. The training method used is Job Instruction Training, which focuses on how to give instructions to operators. The benefits of this program include keeping employees motivated and improving their performance